-ولاية المرأة في عقد الزواج بين الفقه الإسلامي وقانون الأحوال الشخصية الأردني واتفاقية سيدا-دراسة مقارنة - ابوصليح, حمزة احمد (University of Eloued جامعة الوادي, 2021)
جاءت هذه الدراسة لبيان موقف الفقه الإسلامي وقانون الأحوال الشخصية الأردني واتفاقية سيداو من موضوع غاية في الأهمية وهو ولاية المرأة في عقد الزواج ، وبيان أوجه القصور في التشريع الأردني وبيان أوجه مخالفة اتفاقية سيداو فيما يخص موضوع البحث لأحكام الشريعة الإسلامية بمختلف مذاهبها . ولقد اشتملت الدراسة على تمهيد تحدثت فيه عن التعريف بولاية المرأة في عقد الزواج وثلاثة مباحث : تحدثت في المبحث الأول عن ولاية المرأة في عقد الزواج في الفقه الإسلامي وتحدثت في المبحث الثاني عن ولاية المرأة في عقد الزواج في قانون الأحوال الشخصية الأردني رقم 15 لعام 2019 وتحدثت في المبحث الثالث عن ولاية المرأة في عقد الزواج في اتفاقية سيداو . وختمت الدراسة بمجموعة من النتائج كان من أهمها : لم ينص قانون الأحوال الشخصية الأردني رقم 15 لعام 2019 صراحةً على أحقية المرأة البكر البالغة العاقلة بتزويج نفسها بدون إذن وليها أو على عدم أحقيتها بذلك . ولكنه نص على أن المرأة الثيب العاقلة المتجاوزة من العمر ثمانية عشر سنة لا يشترط موافقة وليها في زواجها . ولقد خالفت اتفاقية سيداو أحكام الشريعة الإسلامية في كثير من المواضيع ومن ضمنها ولاية المرأة في عقد الزواج ولم تتفق حتى مع المذهب الحنفي في هذا الموضوع . ولقد اتبعت في الدراسة المنهج التحليلي والاستقرائي في جمع المادة العلمية من المراجع ، والاستفادة من الثروة الفقهية والقضائية ، وسرت على المنهج الاستنباطي في تأصيل الدراسة تأصيلا شرعيا ، وتوثيق أقوال الفقهاء وآرائهم من المصادر المعتبرة لكل مذهب ، وتطرقت للمنهج النقدي في بعض الأحيان Summary This study comes to explain the position of Islamic jurisprudence and the Jordanian personal status law and CEDAW agreement from a very important topic which is the guardianship of women in the marriage contract, and to clarify the deficiencies in the Jordanian legislation and to clarify the aspects of breaching the CEDAW agreement in relation to the topic of research and Islamic law in its various doctrines . The study included a preamble in which she talked about the definition of a woman’s mandate in the marriage contract and three topics: she spoke in the first topic about the woman’s mandate in the marriage contract in Islamic jurisprudence and spoke in the second topic about the woman’s mandate in the marriage contract in Jordanian Personal Status Law No. 36 of 2010 and spoke In the third topic on womens guardianship in the marriage contract in CEDAW. The study concluded with a set of findings Among the most important of these: The Jordanian Personal Status Law No. 36 of 2010 did not explicitly stipulate the right of a rational adult virgin woman to marry herself without the permission of her guardian, or that she was not entitled to do so. But it stipulated that a vicious, rational woman over the age of eighteen years does not require the consent of her guardian in her marriage. CEDAW has contravened the provisions of Islamic law in many matters, including the guardianship of women in the marriage contract, and it did not even agree with the Hanafi school of thought on this matter. In the study, I followed the analytical and inductive approach in collecting scientific material from references, and benefiting from the jurisprudential and judicial wealth. Key words: guardianship of women, marriage contract, Islamic jurisprudence, personal status.
Guardianship of a Woman in a Marriage Contract between Islamic Jurisprudence, the Jordanian Personal Status Law and CEDAW Agreement (Comparative Study)
مقال
Keywords: ولاية المرأة ، عقد الزواج ، الفقه الإسلامي ، الأحوال الشخصية; guardianship of women, marriage contract, Islamic jurisprudence, personal status